2021
DOI: 10.22190/teme200525036s
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Green Bonds on Contemporary Financial Market

Abstract: Since the onset of the global financial crisis at the end of 2008 green projects are becoming increasingly important, and green economy is becoming more and more interesting as an area of research for numerous authors. In this regard, the paper will analyze green bonds that represent an integral part of green finances, i.e. a significant instrument of green economy and a useful mean in fighting climate changes. These securities mostly represent non-taxable financial instruments and have high credit rating, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of environmental loans, the UniCredit group is the leader, followed by the Intesa SanPaolo group, Raiffeisen Bank International, and the ProCredit group. It can be concluded that green projects are becoming increasingly important (Stojkovic, Jovanovic-Kranjec & Lukovic, 2021).…”
Section: Overview Of Sustainable Bankingmentioning
confidence: 99%
“…In terms of environmental loans, the UniCredit group is the leader, followed by the Intesa SanPaolo group, Raiffeisen Bank International, and the ProCredit group. It can be concluded that green projects are becoming increasingly important (Stojkovic, Jovanovic-Kranjec & Lukovic, 2021).…”
Section: Overview Of Sustainable Bankingmentioning
confidence: 99%